Ever Changing Times: Sustainability Transformations of Galician Small-Scale Fisheries - Villasante, Sebastián; Tubío, Ana; Gianelli, Ignacio; Pita, Pablo; García-Allut, Antonio (Frontiers in Marine Science, 2021)
The Galician small-scale fisheries sector has been experiencing important changes. The presence of a wide range of ecological, economic, social and institutional drivers have forced the statu quo toward new transitions with the potential to generate desirable transformative changes. Sustainability transformations mean that changes fundamentally alter the entire system’s ecological and/or social properties and functions. However, there is a limited understanding of how a transformative change may look in small-scale fisheries, when and by whom it can be triggered, supported, and implemented. To cover this research gap, the objectives of this paper are twofold: to document the current state of the art of Galician small-scale fisheries, and to evaluate the innovations and changes that occurred between 1990 and 2020, to explore whether such changes have scaled-up as seeds of desirable transformative changes and, if not, what obstacles and/or barriers have been identified in the scientific literature. We selected two cases, the Galician shellfisheries and the Marine Protected Area of Fishing Interest Os Miñarzos, to understand when and how profound changes in small-scale fisheries took place. We hypothesize that obstacles for building resilience to consolidate transformative changes once triggered are the still moderate effectiveness of the fisheries management systems, the low progress of incorporation of scientific and traditional knowledge into decision-making processes and policy arenas, the lack of studies about socio-economic contribution to coastal communities and commercialization models, and the presence of persistent ecological and economic drivers hindering desirable transformative changes.